Colposcopy Evaluation at the Time of Loop Electrosurgical Excision Procedure May Avoid Unnecessary Treatment. Issue 4 (October 2018) - Munmany, Meritxell; Torné, Aureli; Nonell, Roser; Barnadas, Esther; Luqui, Nerea; Ordi, Jaume; del Pino, Marta
Abstract : Objective: The aim of the study was to assess the accuracy of colposcopy evaluation at the time of the loop electrosurgical excision procedure (LEEP) to identify women with a previous confirmatory diagnosis of squamous intraepithelial lesion/cervical intraepithelial neoplasia (SIL/CIN) with low probability of dysplasia in the LEEP specimen. Materials and Methods: We prospectively recruited a cohort of 162 women undergoing LEEP for histological high-grade SIL/CIN 2–3 or low-grade SIL/CIN 1 with high-grade SIL cytology showing a fully visible squamocolumnar junction in the colposcopy evaluation at the time of LEEP. At the referral visit cervical cytology, human papillomavirus and genotype detection, digital colposcopy, colposcopical lesion measurement, and 1 or more biopsies of the transformation zone were obtained. The uterine cervix was colposcopically evaluated intraoperatively. Results: Thirty-four women (21.0%) had a normal colposcopy evaluation at the time of the LEEP, whereas the remaining 128 women showed abnormal findings. Absence of SIL/CIN in the LEEP specimen was confirmed in 28 (82.3%) of the 34 women with a normal colposcopy at the time of LEEP group and 8 (3.1%) of the 128 women showing abnormal colposcopy at the time of LEEP group ( p < .001). A normal colposcopic evaluation at the time of LEEP was associated with an increase in the risk of absence of lesion in the cone specimen compared with cases presenting an abnormal colposcopy (95% CI = 33.8–1, 555.1, p < .001). The colposcopy evaluation at the time of LEEP had a positive predictive value of 82.3% (95% CI = 66.5–91.5) and a negative predictive value of 96.9% (95% CI = 92.2–98.8) to predict low probability of SIL/CIN in the specimen. Conclusions: Colposcopic evaluation at the time of LEEP seems to be accurate to identify SIL/CIN postbiopsy regression; thus, its performance would be considered at the time of the treatment.